Critical Coordination Factors Affecting Design and Build Projects: A Comprehensive Review of the Literature - Ohag, Misbah; Nawawi, Abdul Hadi; Muhammad, Faudzi; Hashim, Norfashiha (International Journal of Environment, Architecture, and Societies, 2023)
The design and build projects (DB) have increased in numbers in the last few decades. DB method is becoming more popular than the traditional method in Malaysia, especially in national projects.However, design-build projects may suffer from a significant number of problems, such as conflicts between the project parties (designers, contractors, and owners), resulting in poor performance and poor quality. One common cause of project failure of conventional projects is poor coordination and communication process. It has been found that no such study has been found to identify the coordination factors that might affect the project’s success. To fill this gap, this research aims to establish a framework of coordination factors affecting DB projects’ performance in Malaysia. This study uses a mixed methodology approach to identify critical coordination factors by a comprehensive review of the literature. The identified factors were categorized, ranked, and prioritized according to their influence on project performance using a quantitative approach. It is found that scheduling and planning, human resource coordination, documentation & records coordination, contract implementation coordination, value engineering and quality assurance, technical coordination, design coordination, management coordination, and external coordination are the significant factors of coordination that may affect the performance of construction projects. This study provides empirical evidence by correlating the identified coordination factors with DB project performance. Identification of coordination factors will help in enhancing and improving the performance of design and build projects.